Characteristics of Aphasia in Ischemic Stroke Patients at a National Brain Center in Indonesia - Rasya Hapsari Danardhono; Arman Yurisaldi Saleh; Ria Maria Theresa; Riezky Valentina Astari (Folia Medica Indonesiana, 2023)
Highlights: